Prevalence and clinical characteristics of human metapneumovirus infections in hospitalized infants in Spain - García‐García, M.L. (Pediatr Pulmonol, 2006)
Human metapneumovirus (hMPV), a condition recently described in the Netherlands, causes lower respiratory infections, particularly in young children and among the elderly. The objective of this study was to describe the characteristics of hMPV infections in hospitalized infants <2 years of age and to compare them to those of infections caused by respiratory syncytial virus (RSV). A prospective study was conducted on the clinical characteristics of infants admitted to hospital for respiratory infection through 5 years. Simultaneous detection of influenza A, B, and C viruses, RSV, and adenoviruses was performed in clinical samples by multiple reverse transcription nested‐PCR assay. The presence of hMPV was tested in all samples using two separate RT‐PCR tests. Some respiratory virus was detected in 70.5% of the 1,322 children included in the study. hMPV was found in 101 of the positive nasopharyngeal aspirates (10.8%), and was the most common virus after RSV and rhinovirus. Peak incidence was found in March. Over 80% of children were <12 months. The more common diagnoses were bronchiolitis (49.5%) and recurrent wheezing (45.5%). Fifty‐four percent of cases required oxygen therapy and, one percent, assisted ventilation. Thirty percent were co‐infections, with clinical characteristics indistinguishable from single infections. Seventy‐one hMPV single infections were compared to 88 RSV single infections. hMPV infections were significantly more frequent than RSV in infants older than 6 months (P = 0.04). Recurrent wheezing was diagnosed more frequently in hMPV patients (P = 0.001). All other variables tested were similar, in both groups. hMPV was the third most frequent virus after RSV and rhinovirus in infants <2 years of age, hospitalized for respiratory infection, and was associated with bronchiolitis and recurrent wheezing. hMPV predominantly occurred in spring. Co‐infections were frequent and clinically similar to single infections and RSV infections. Pediatr Pulmonol. © 2006 Wiley‐Liss, Inc.